2015
DOI: 10.1103/physrevb.92.155407
|View full text |Cite
|
Sign up to set email alerts
|

Silicene multilayers on Ag(111) display a cubic diamondlike structure and a3×3reconstruction induced by surfactant Ag atoms

Abstract: The structure of silicene multilayers grown on Ag(111) and the nature of their √ 3 × √ 3 R30 • reconstruction were studied by low-energy electron diffraction, Auger spectroscopy, and optical reflectance methods. It is shown that the surface reconstruction is induced by a surfactant layer of silver atoms during the growth of the silicon film and is not due to pristine Si. The Si film displays the optical characteristics of bulk cubic diamondlike Si, which indicates that it is not formed by any other allotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 69 publications
4
37
0
Order By: Relevance
“…An apparent exception, with experiments performed in the low temperature regime, is the work of Borensztein et al [31]. Yet, we stress that for simplicity, they improperly adopted a laminar growth model, which is at variance with the well-established terrace growth [18,20,33,45].…”
mentioning
confidence: 85%
“…An apparent exception, with experiments performed in the low temperature regime, is the work of Borensztein et al [31]. Yet, we stress that for simplicity, they improperly adopted a laminar growth model, which is at variance with the well-established terrace growth [18,20,33,45].…”
mentioning
confidence: 85%
“…Such thick Si films were first addressed to as "multi-layer silicene"; however, further studies revealed their diamond bulklike structure and the surfactant behaviour of silver atoms [33][34][35]. The determination of the atomic structure of the reconstructions is of profound interest, being closely related to the electronic bands simulated by DFT calculation.…”
Section: Introductionmentioning
confidence: 99%
“…This is shown in Fig. , where the experimental curve is very well reproduced by the calculation performed for a mixing of bulk crystalline Si (corresponding to the central part of the film) and of amorphous Si (corresponding to the interface and the surface monolayers) . The derivative‐like feature around 3.4 eV is typical of the E o ′/ E 1 electronic transition of bulk Si, which is not expected for a silicene multilayer (the feature at 3.8 eV is due to the contribution of Ag, seen through the thin Si film).…”
Section: Silicene Layers On Ag(111)mentioning
confidence: 53%
“…It has been proposed that the formation of silicene multilayers could permit to overcome this obstacle, by isolating the upper layers of silicene from the metallic substrate . However, recent results showed that such silicene multilayers are likely bulk diamond‐like silicon, which is the only known bulk allotropic phase of silicon . In particular thermoreflectance spectra, which are the relative change of reflectance upon temperature change, measured on a 2.1 nm silicon film grown on Ag(111) at 479 K, display the typical features of diamond‐like Si.…”
Section: Silicene Layers On Ag(111)mentioning
confidence: 99%